2005
DOI: 10.1089/clo.2005.7.119
|View full text |Cite
|
Sign up to set email alerts
|

Progeny of Somatic Cell Nuclear Transfer (SCNT) Pig Clones Are Phenotypically Similar to Non-Cloned Pigs

Abstract: Systematic studies of cloned animals generated from adult somatic cell nuclei are critical in assessing the utility of somatic cell cloning in various applications, including the safety of food products from cloned animals and their offspring. Previously, we compared somatic cell derived cloned pigs with naturally bred control pigs on a series of physiological and genetic parameters. We have extended our studies to the F1 progeny of these clones to see whether these phenotypic differences are transmitted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
6
18
0
Order By: Relevance
“…When the results of routine serum biochemistry and hematology of the Japanese Black breed calf produced here were compared with those of its herd mate, no abnormal values were found in either animal. Similarly, analysis of piglets produced by mating pairs of cloned pigs did not reveal any abnormal values in the serum biochemistry results for creatinine, alkaline phosphatase, blood urinary nitrogen, albumin, phosphatase, calcium, serum protein, or glucose [13]. These results appear to support the hypothesis that the progeny of pairs of clones are similar to those of naturally bred animals.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…When the results of routine serum biochemistry and hematology of the Japanese Black breed calf produced here were compared with those of its herd mate, no abnormal values were found in either animal. Similarly, analysis of piglets produced by mating pairs of cloned pigs did not reveal any abnormal values in the serum biochemistry results for creatinine, alkaline phosphatase, blood urinary nitrogen, albumin, phosphatase, calcium, serum protein, or glucose [13]. These results appear to support the hypothesis that the progeny of pairs of clones are similar to those of naturally bred animals.…”
Section: Discussionsupporting
confidence: 56%
“…To quantify the risk, it is clearly essential to study the offspring produced by cloned dams and sires. To date, however, the available information is limited to two studies, one in cattle [12] and the other in pigs [13].…”
mentioning
confidence: 99%
“…It has been reported that, in SCNT, embryo losses occur at various stages, and the anomalies in fetal and perinatal stages have been observed [1][2][3][4][5][6]. Because such abnormalities of clones are not transmitted to their progenies [7][8][9][10][11][12], most of the developmental problems of clones are believed to be the results of epigenetic defects [13]. In fact, several studies have revealed abnormal epigenetic modifications such as DNA methylation and histone modifications in SCNT embryos [14][15][16][17].…”
mentioning
confidence: 99%
“…In pigs, Shibata et al [4] and Hu et al [5] reported that cloned pigs and their offspring were similar to others of the same breed in growth, reproduction and meat production [6]. The reproductive characteristics of cloned boars are highly comparable to naturally produced boars [7,8].…”
Section: Introductionmentioning
confidence: 93%